2020
DOI: 10.1371/journal.pone.0236781
|View full text |Cite
|
Sign up to set email alerts
|

Bach1 promotes muscle regeneration through repressing Smad-mediated inhibition of myoblast differentiation

Abstract: It has been reported that Bach1 -deficient mice show reduced tissue injuries in diverse disease models due to increased expression of heme oxygenase-1 (HO-1)that possesses an antioxidant function. In contrast, we found that Bach1 deficiency in mice exacerbated skeletal muscle injury induced by cardiotoxin. Inhibition of Bach1 expression in C2C12 myoblast cells using RNA interference resulted in reduced proliferation, myotube formation, and myogenin expression compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
(81 reference statements)
2
7
0
Order By: Relevance
“…Smad2 is an important effector of the TGF-β signaling cascade in response to TGF-βs stimulation (containing MSTN). MSTN interacts with receptors, which triggers Smad2 and Smad3 phosphorylation, subsequently forming a complex of the phosphorylated Smad2/3 and Smad4 in the nucleus to regulate skeletal muscle development. , Recent studies have also reported that activation of endogenous Smad2 can lead to muscle atrophy, whereas inhibition of Smad2 can promote myogenic differentiation. Similarly, we found that Smad2 overexpression significantly inhibited the differentiation of C2C12 myoblasts, whereas knockdown of endogenous Smad2 promoted their differentiation. In addition, we also verified a Smad2 -mediated effect of miR-455-3p on differentiation by cotransfecting miR-455-3p mimics and Smad2 -overexpressing plasmids.…”
Section: Discussionsupporting
confidence: 59%
“…Smad2 is an important effector of the TGF-β signaling cascade in response to TGF-βs stimulation (containing MSTN). MSTN interacts with receptors, which triggers Smad2 and Smad3 phosphorylation, subsequently forming a complex of the phosphorylated Smad2/3 and Smad4 in the nucleus to regulate skeletal muscle development. , Recent studies have also reported that activation of endogenous Smad2 can lead to muscle atrophy, whereas inhibition of Smad2 can promote myogenic differentiation. Similarly, we found that Smad2 overexpression significantly inhibited the differentiation of C2C12 myoblasts, whereas knockdown of endogenous Smad2 promoted their differentiation. In addition, we also verified a Smad2 -mediated effect of miR-455-3p on differentiation by cotransfecting miR-455-3p mimics and Smad2 -overexpressing plasmids.…”
Section: Discussionsupporting
confidence: 59%
“…Most DNA target sites identified in the distal silencer (-1424/-2000) by the TFSEARCH analysis have been reported to bind TFs such as AREB6, ARP-1, Bach1 and Evi1 (Supplementary Table S2), which have been reported to function as transcriptional repressors [90][91][92][93][94][95]. Therefore, the repressive action of these TFs, once they have bound to their target sites in the CLU silencer, may, at least in part, contribute to the differential expression observed for the CLU gene in our hTEC model.…”
Section: Discussionmentioning
confidence: 99%
“…Myostatin is synthesized and secreted primarily by skeletal muscle cells and signals through the activin-type II receptor (ActRII) [ 18 ]. ActRII recruits an Alk family kinase, leading to the activation of the small mother against decapentaplegic (Smad) 2/3 transcription factor complex that mediates inhibition of genes associated with muscle differentiation [ 19 ]. A study by Conery and colleagues documented that activation of Akt downregulates ActRIIB, blocking the atrophy-inducing effects of the constitutively active activin receptor-like kinase (ALK) 4/5 [ 20 ].…”
Section: Cellular Processes Involved In Muscle Mass Homeostasismentioning
confidence: 99%